High physical and psychosocial load at work and sickness absence due to neck pain - Ariëns, Geertje AM; Bongers, Paulien M.; Hoogendoorn, Wilhelmina E.; van der Wal, Gerrit; van Mechelen, Willem (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'This study investigates the relationship between physical and psychosocial load at work and sickness absence due to neck pain. ' ' METHODS ': 'A prospective cohort study with a follow-up period of 3 years (1994-1998) was performed among a working population. At the beginning of the study, physical load at work was quantified by means of video recordings. Work-related psychosocial variables were measured by means of the Job Content Questionnaire. The frequency of sickness absence due to neck pain with a minimal duration of 3 days was assessed on the basis of company registrations during the follow-up period. Altogether 758 workers were included in the analyses. Possible confounding by individual characteristics, physical load, and psychosocial load was studied. ' ' RESULTS ': 'Work-related neck flexion and neck rotation, low decision authority, and medium skill discretion showed statistically significant increased risks for sickness absence due to neck pain (adjusted rate ratios ranging from 1.6 to 4.2). High quantitative job demands, low skill discretion, and low job security showed nonsignificant increased risks for sickness absence due to neck pain (adjusted rate ratios of 2.0, 1.6 and 1.7, respectively). Work-related sitting, conflicting job demands, supervisor support, and co-worker support did not increase sickness absence due to neck pain. ' ' CONCLUSIONS ': 'Work-related neck flexion, neck rotation, low decision authority, and medium skill discretion are risk factors for sickness absence due to neck pain. There are indications that high job demands, low skill discretion, and low job security are also risk factors for sickness absence due to neck pain.
Keywords: cervical spine; longitudinal study; neck pain; physical load; prospective cohort study; psychosocial load; risk factor; sick leave; sickness absence; work; work-related neck pain; work-related physical load; work-related psychosocial load